Identifikasi Tanaman Obat-Obatan Sebagai Elemen Lunak Lansekap di Kecamatan Kediri, Kabupaten Tabanan, Provinsi Bali - PARAMITA, LUH RATIH; SARWADANA, SANG MADE; ASTAWA, I NYOMAN GEDE (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017DO - 10.24843/JAL.2017.v03.i02.p01, 2017)
Indonesia is an agricultural country known for the wealth of species and different kinds of plants. Diversity of natural resources make Indonesia has a lot of biodiversity as well as the diversity of traditional medical plants, or more commonly known herbs.Medical plants flowering in the regional in Kediri, Tabanan regency, Province of Bali still very little is used as an softscape element of landscape, so it has not been used optimally. Presumably there are many kinds of medical plant other throughout in Kediri, Tabanan regency, Province of Bali either cultivated or growing wild. Have data regarding a kinds of medical plants in the region is very important both for science and conservation. Medical plants have potential as an ornamental plant, because the flowers can give a feeling of luxury, so there will be a sense of pride by the owner. Medical plants can be used as landscape softcape elements, besides being able to used aesthetics value of the plants and when necessary for health will be easier to get it. This method of technique sampling used survey, questionnaires, and interview. The results of this those there are 52 species of medical plants which are grouped into five flowering habitus are bushes, shrubs, water plants, trees, and ground cover.There are four function of medical plants has inventory and identification as an element of landscape design is as a railings, shade, absorbing pollutants and aesthetics value.